Public Higher Education Funding, Budget Drivers, and Related Issues: The State Community College Director Perspective - Stephen G. Katsinas; Mark M. D’Amico; Janice N. Friedel (Educational Considerations, 2014)
This article presents results from the 2012 National Survey of Access and Finance Issues conducted by the National Council of State Directors of Community Colleges (NCSDCC), an affiliated council of the American Association of Community Colleges, and includes a comparison of survey results from previous years dating back to 2003, with the exception of 2005 and 2006 when the survey was not conducted.
Keywords: Community Colleges; elementary; secondary; education; American Recovery and Reinvestment Act (ARRA); challenges; maintenance; Higher Education; budget; issues